2011
DOI: 10.1038/protex.2011.224
|View full text |Cite
|
Sign up to set email alerts
|

Rate-­‐controlled Cryopreservation and Thawing of Mammalian Cells

Abstract: Cryopreservation is the use of very low temperatures to preserve structurally intact living cells. Mammalian cells are cryopreserved to avoid loss by contamination, to minimize genetic change in continuous cell lines, and to avoid transformation in finite cell lines. The cells which survive the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…18,20,25,4042 These solutions are non-toxic and easily soluble and are thought to prevent such injury via several proposed mechanisms. 18,20,22,25,4044 They can partially solubilize the cell membrane so that it is less prone to puncture and interrupt the lattice of the ice, so that fewer intracellular crystals form. Cryoprotectants also increase the solute concentration in cells thus lowering the glass transition temperature (for water is −135C) of a solution below which molecular movement ceases and all biological activity is suspended thus preventing actual freezing and the cytosol maintains some flexibility in a glassy phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,20,25,4042 These solutions are non-toxic and easily soluble and are thought to prevent such injury via several proposed mechanisms. 18,20,22,25,4044 They can partially solubilize the cell membrane so that it is less prone to puncture and interrupt the lattice of the ice, so that fewer intracellular crystals form. Cryoprotectants also increase the solute concentration in cells thus lowering the glass transition temperature (for water is −135C) of a solution below which molecular movement ceases and all biological activity is suspended thus preventing actual freezing and the cytosol maintains some flexibility in a glassy phase.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent such freezing injury various cryoprotectants such as glycerol, ethanediol, propanediol and dimethyl sulfoxide (DMSO) have been used for stable freezing and long-term preservation of established cell lines and tissues. 2227 Cryopreservation of primary patient tumor and subsequent PDX has been investigated previously, but the efficacy of reanimation has typically been low, or not reported. 23,24,28,29 Cryopreservation of composite tissues, such as PDX tumors, is more complex than for homogenous cell lines as a three-dimensional architecture needs to be maintained during both freezing and thawing.…”
Section: Introductionmentioning
confidence: 99%
“…In SF, a phase transition occurs from liquid to solid on temperatures below freezing point. Slow-cooling protocols involve the use of <1.0 M of cryoprotective agents (CPAs), such as glycerol or dimethyl sulphoxide (DMSO), which have minimal toxicity at lower temperatures with the use of a high-cost controlled rate freezer or a benchtop portable freezing container [21].…”
Section: Slow Freezingmentioning
confidence: 99%
“…There are two methods in the cryopreservation of embryo: vitrification and programmed slow freezing (Arav 2014). In literature, some considerations were identified in the programmed slow freezing, Thompson et al (2011) indicated that subjecting embryos to a rate of 1 °C min -1 is considered a typical cooling rate for mammalian embryos. Despite the huge costs, equipment, and multiple steps of slow freezing, it has been observed a decrease in both survival and implantation rates (Bromfield et al 2009).…”
Section: Introductionmentioning
confidence: 99%